Evaluasi Pelaksanaan Pemilihan Kepala Desa Di Kecamatan Rantau Bayur Kabupaten Banyuasin - Putra, Ruddy Permana; Sakir, Icuk Muhammad; Zuber, Konar (@-Publik: Jurnal Administrasi Publik, 2025)
The Village Head has a strategic role in preparing and implementing village development plans and managing the resources and budget owned by the village. Therefore, the village head election process must be carried out in a transparent, fair and accountable manner to ensure the election of quality leaders who are ready to serve the community. The problems that occur include limited community access to information about village head candidates, their vision and mission, and work programs that can hinder voters from making informed and wise decisions. Lack of oversight and transparency in the village head election process can create opportunities for interference and fraud. Democracy is a form of government in which all citizens have equal opportunities or equal rights in making decisions to determine the future of their lives. This study is assessing the implementation of village head elections in Rantau Bayur District, Banyuasin Regency. The main objective of implementing village head elections is to elect village heads who have integrity, capability, and dedication to serve the village community. With a fair and democratic village head election, it is hoped that village communities will have leaders who are able to advance the village and create prosperity for all its citizens. The research approach used is a qualitative descriptive approach. The results of the CIPP model evaluation research show that the implementation of village head elections must be carried out in a transparent and accountable manner to get leaders who are in accordance with the needs of the community with the context, input, process and product where the implementation of village head elections in Rantau Bayur District, Banyuasin Regency has gone well.